1991
DOI: 10.1002/ijc.2910480410
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progesterone receptors in cervical human papillomavirus related lesions

Abstract: According to recent studies showing that human papillomavirus (HPV) infections can be influenced by sex steroid hormones, we performed estrogen (ER) and progesterone (PgR) receptor assays in fresh frozen biopsies of genital-HPV-related lesions. Seventy-three women with normal cervix, condyloma, low- and high-grade CIN and squamous carcinoma were evaluated in comparison with 15 persons with vulvar and 9 with penile papillomavirus-associated lesions. HPV genotypes were determined by dot-blot hybridization. Non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
0
5

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 22 publications
3
47
0
5
Order By: Relevance
“…This result is similar to that obtained in previous studies in which ER expression was found to be inversely associated with disease status (8,9,12). On the other hand, a similar ER distribution was observed in the stroma of both tumors and normal tissues.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…This result is similar to that obtained in previous studies in which ER expression was found to be inversely associated with disease status (8,9,12). On the other hand, a similar ER distribution was observed in the stroma of both tumors and normal tissues.…”
supporting
confidence: 92%
“…For progesterone receptors (PR) the variation is even wider, i.e., 0 to 100% of tissues from the uterine cervix have been reported to be PR positive (8)(9)(10)(11)(12). No statistically significant correlations have been found for the ER/PR ratio in the cervix when related to menstrual cycle, menopause, histological type or ploidy analysis (8)(9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although endometrial expression of estrogen and progesterone receptors has been shown to vary during the menstrual cycle (Fujishita et al, 1997;Ravn et al, 1994), no significant difference was demonstrated in hormone receptor-positive cell density between the follicular and luteal phases in both TZ and ectocervical biopsies (Remoue et al, 2003). These data are in agreement with previous studies showing no significant variation, within the menstrual cycle, in hormone receptor concentrations in vaginal tissues (Schwartz, 2000) and in HPV-associated lesions (Monsonego et al, 1991), suggesting a lower sensitivity to menstrual cycle changes of genital squamous mucosa compared to glandular endometrial tissues.…”
Section: Role Of Sex Hormones In the Induction Of Squamous Metaplasiasupporting
confidence: 91%
“…The expression of sex hormone receptors in human cervical biopsies has also been shown to be higher in the precancerous TZ compared to normal ectocervix and to increase with the grade of SIL, strengthening the hormone-dependent establishment of cervical (pre)neoplastic lesions (Monsonego et al, 1991).…”
Section: Role Of Sex Hormones In the Induction Of Squamous Metaplasiamentioning
confidence: 93%